2024
DOI: 10.1038/s41586-024-07033-8
|View full text |Cite
|
Sign up to set email alerts
|

Signatures of a surface spin–orbital chiral metal

Federico Mazzola,
Wojciech Brzezicki,
Maria Teresa Mercaldo
et al.

Abstract: The relation between crystal symmetries, electron correlations and electronic structure steers the formation of a large array of unconventional phases of matter, including magneto-electric loop currents and chiral magnetism1–6. The detection of such hidden orders is an important goal in condensed-matter physics. However, until now, non-standard forms of magnetism with chiral electronic ordering have been difficult to detect experimentally7. Here we develop a theory for symmetry-broken chiral ground states and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Hence, our scheme can also detect strongly localized Berry curvatuer as long as (i) inter-band transitions can be induced in the relevant region, and (ii), in the case of excitonic transitions, the exciton wave function has signifcant overlap with the relevant region in momentum space. The surface sensitivity furthermore enables the extraction of chiroptical signatures for the emerging field of Berry curvature engineering at surfaces ( 48 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, our scheme can also detect strongly localized Berry curvatuer as long as (i) inter-band transitions can be induced in the relevant region, and (ii), in the case of excitonic transitions, the exciton wave function has signifcant overlap with the relevant region in momentum space. The surface sensitivity furthermore enables the extraction of chiroptical signatures for the emerging field of Berry curvature engineering at surfaces ( 48 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of the free electron, the size of the chiral coils is only limited by the de Broglie wavelength and can therefore reach picometer dimensions for applications in atomic or molecular spectroscopy ( 35 , 36 ), electron microscopy ( 37 ), electron acceleration ( 38 ), or free-electron quantum optics ( 28 , 39 ). For example, chiral electron coils should be useful to induce or probe the ring currents in atomic orbitals ( 35 ), large molecules ( 40 ), or magnetic materials ( 41 ). The nanometric electromagnetic field inside of electron coils or other shaped charge densities may be useful for optical tweezers on subnanometer dimensions ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion of spin–orbit coupling seems to be crucial to describe the experimental results obtained by photoemission. We emphasize that magnetic systems with strong spin–orbit coupling might be an important resource to seek for a finite Berry curvature, because the confluence of time-reversal symmetry breaking and spin–orbit coupling (SOC) is at the basis of nontrivial topological properties caused by the Berry curvature itself. In this regard, Fujisawa et al reported that for thicker films of our same composition negative anomalous transport occurs. Thus, even if this goes beyond the scope of our letter, it is interesting to speculate for future works about investigating thin-film materials of Cr 1.6 Te 2 to look for the same phenomenology.…”
mentioning
confidence: 95%